Taxonomic notes on four closely related spider species of the genus Khorata (Araneae, Pholcidae) - Jinglin Li; Baisensen Zhang; Shuqiang Li; Zhiyuan Yao (ZooKeys, 2025)
Khorata Huber, 2005 contains 53 species. It is distributed in the Indo-Malayan region. In this study, a new species is described from Guangxi, China: Khorata qianlei Li, Li & Yao, sp. nov. (♂♀). This new species is similar to K. digitata Yao & Li, 2010 (Guangxi, China; Vietnam), K. qian Yao & Li, 2019 (Guizhou, China), and K. yuhaoi Xu, Zheng & Yao, 2020 (Guizhou and Yunnan, China). Taxonomic keys for distinguishing these four closely related species and a distribution map of all species in this genus are provided. In addition, 37 species of this genus are classified into nine formal species groups.